2013
DOI: 10.2147/ijn.s44342
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake mechanism and intracellular fate of hydrophobically modified pullulan nanoparticles

Abstract: Abstract:The cellular uptake mechanism and intracellular fate of self-assembled nanoparticles (NPs) of cholesterol-modified pullulan (CHSP) by human hepatocellular carcinoma (HepG2) cells were investigated. Covalent conjugation with fluorescein isothiocyanate (FITC) yielded stably labeled CHSP (FITC-CHSP), which was successfully formulated into NPs (mean particle size 63.0 ± 1.9 nm) by dialysis. A cytotoxicity assay clearly indicated that the CHSP NPs did not show significant toxicity in HepG2 cells. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Grafting of hydrophobic segments onto the hydrophilic polymeric backbone leads to amphiphilic polymers which form self-associate thermodynamically stable nanogel structures, with an inner hydrophobic core. Stable in size over time, such polymeric micelles have been recognized as promising drug carriers, the hydrophobic core-shell structure being able to trap hydrophobic drugs ( Liu et al, 2008 ; Bataille et al, 2011 ; Jiang et al, 2013 ). In this respect, the most cited paper was an early work from 1993 on the self-assembly of cholesteryl-bearing pullulan (CHP), forming stable hydrogel nanoparticles, which represented the starting point for future perspective drug-release complexes ( Bataille et al, 2011 ).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Grafting of hydrophobic segments onto the hydrophilic polymeric backbone leads to amphiphilic polymers which form self-associate thermodynamically stable nanogel structures, with an inner hydrophobic core. Stable in size over time, such polymeric micelles have been recognized as promising drug carriers, the hydrophobic core-shell structure being able to trap hydrophobic drugs ( Liu et al, 2008 ; Bataille et al, 2011 ; Jiang et al, 2013 ). In this respect, the most cited paper was an early work from 1993 on the self-assembly of cholesteryl-bearing pullulan (CHP), forming stable hydrogel nanoparticles, which represented the starting point for future perspective drug-release complexes ( Bataille et al, 2011 ).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…[35][36][37][38] Absorption peaks of FITC might be expected between 1400 -1500 cm -1 , corresponding to aromatic ring stretching vibrations. 39 However, the FITC signal is obscured by the protein signals, which are both strong and complex in this region. The FITC-OVA/PLGA particles exhibited the IR bands of both PLGA and OVA, including the ester functional groups of PLGA (1084, 1174, 1270, and 1752 cm -1 ) and the protein amide region (1534 and 1654 cm -1 ).…”
Section: Particle Characterizationmentioning
confidence: 99%
“…41 In vitro release studies were performed using the shaking method, commonly employed to study the release kinetics of microparticles. 26,[39][40] The cumulative release and concentration profiles of the FITC-OVA/PLGA particles are given in .70 % of the total release) was initially evident. This was followed by fluctuation of the protein concentration over the range from 2.5 ± 0.6 μg/mL (ca.…”
Section: Drug Loading and Releasementioning
confidence: 99%
“…116 The caveolae-mediated endocytosis pathway is characteristic by the evolution of caveolae-derivatives of the subdomains of sphingolipid and cholesterol-rich cell membrane fractions, which mediates the translocation to the Golgi apparatus, to endoplasmic reticulum or entered into the endosomal pathway. 117 It has been revealed that the pathway of nanoparticles into cells can be regulated by shape. For instance, Hao et al 105 used sphere-nanoparticles (NS), short-rod nanoparticles (NSR), and Their results preliminarily demonstrated that NS particles preferred to be internalized into cells via the clathrinmediated pathway, whereas the uptake is shifted to the caveolae-mediated pathway for the particles with large aspect ratios (ARs).…”
Section: Effects Of Nanoparticle Morphology On Cellular Uptake In Vivmentioning
confidence: 99%
“… 116 The caveolae-mediated endocytosis pathway is characteristic by the evolution of caveolae-derivatives of the subdomains of sphingolipid and cholesterol-rich cell membrane fractions, which mediates the translocation to the Golgi apparatus, to endoplasmic reticulum or entered into the endosomal pathway. 117 …”
Section: The Effect Of Shape For Oral Bioavailabilitymentioning
confidence: 99%